2010
DOI: 10.1007/s11605-010-1326-4
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Mortality After Pancreatic Cancer Resection

Abstract: In-hospital and 30-day mortality after resection for cancer are similar nationally; thus, comparing mortality utilizing these measures is acceptable. After a 60-day post-resection window of increased mortality, mortality risk then continues at a constant rate over 2 years, suggesting that mortality after pancreatectomy is not limited to early ("complication") and late ("cancer") phases. Determining ways to decrease perioperative mortality in the 60-day interval will be critical to improving overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…Therefore, possibly more elderly patients in the Netherlands could benefit from pancreatic surgery [2,10]. Several studies on surgical risks of patients with gastrointestinal cancers showed that postoperative mortality prolonged beyond the 30-day postoperative period [3,[19][20][21]. In a recent study, a doubling of the 30-day mortality rate after pancreatic surgery was found by 90 days postoperative [3].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, possibly more elderly patients in the Netherlands could benefit from pancreatic surgery [2,10]. Several studies on surgical risks of patients with gastrointestinal cancers showed that postoperative mortality prolonged beyond the 30-day postoperative period [3,[19][20][21]. In a recent study, a doubling of the 30-day mortality rate after pancreatic surgery was found by 90 days postoperative [3].…”
Section: Discussionmentioning
confidence: 99%
“…2 Of those who do, some may quickly succumb to recurrent disease or develop postoperative complications. [3][4][5][6] Abdominal imaging is widely used in the resected pancreatic cancer population. In addition to evaluating patients with new symptoms or complications, many physicians also perform serial imaging at routine intervals to evaluate for recurrent disease.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative mortality is strictly dependent on the type of procedure and the hospital resection volume [6,7,11,12,13,14]. The majority of NF-PETs are resectable with a distal or a limited pancreatectomy and often with enucleation [3,4,5].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of NF-PETs are resectable with a distal or a limited pancreatectomy and often with enucleation [3,4,5]. Mortality resulting from a distal pancreatectomy is reported to be at most 1-2% [12,13,14]. In the present study, baseline 30-day mortality was assumed to be 1.5% [12] and ranged from 0 to 3% [13,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation